Cognitive reserve over life course and 7-year trajectories of cognitive decline: results from China health and retirement longitudinal study - Xuanji Chen; Baowen Xue; Yaoyue Hu (BMC, 2022)
Abstract Background Cognitive reserve (CR) could partly explain the individual heterogeneity in cognitive decline. No study measured CR from a life course perspective and investigated the association between CR and trajectories of cognitive decline in older Chinese adults. Methods Data of 6795 Chinese adults aged 60+ from China Health and Retirement Longitudinal Study were used. Global cognition score (0-32) was assessed in all four waves. A life-course CR score was constructed using markers of childhood circumstance, education, highest occupational class, and leisure activities in later life. Latent growth curve modelling (LGCM) was applied to assess the association between CR and trajectories of cognitive decline. Results For the life-course CR, factor loadings of markers in adulthood and later life were larger than that of markers in childhood. The life-course CR score (ranged between − 2.727 and 6.537, SD: 1.74) was higher in urban Chinese adults (0.75, SD: 1.90) than in rural Chinese adults (− 0.50, SD: 1.43). The unconditional LGCM results showed that urban older Chinese adults had better global cognition at baseline (intercept: 15.010, 95% CI: 14.783, 15.237) and a slower rate of cognitive decline per year (linear slope: -0.394, 95% CI: − 0.508, − 0.281) than their rural counterparts (intercept: 12.144, 95% CI: 11.960, 12.329; linear slope: -0.498, 95% CI: − 0.588, − 0.408). After controlling for all covariates, one-unit higher CR score was associated with 1.615 (95% CI: 1.521, 1.709) and 1.768 (95% CI: 1.659, 1.876) unit higher global cognition at baseline for urban and rural older Chinese adults, respectively. The slower rate of cognitive decline associated with higher CR was more evident in rural residents (slope: 0.083, 95% CI: 0.057, 0.108) than in their urban counterparts (0.054, 95% CI: 0.031, 0.077). Conclusions CR was associated with better baseline cognition and slower cognitive decline in Chinese older adults. Although rural residents were disadvantaged in both CR and cognition, the protective effect of CR against cognitive decline was stronger for them than in those who live in urban area.